1998
DOI: 10.2307/1161147
|View full text |Cite
|
Sign up to set email alerts
|

The chief, the mine captain and the politician: legitimating power in northern Ghana

Abstract: This article explores the strategies of acquiring and legitimating power in Ghana, taking the example of three ‘big men’ from the north, a paramount chief, a mine captain and a politician in the making. After offering some observations on the recent public debate on the (im)morality of power and ‘bigness’, it outlines the biographies of these three ‘big men’ and analyses how they skilfully combine different registers of power and legitimacy. It then analyses the strategies of legitimation and grounds of moral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 9 publications
0
45
0
1
Order By: Relevance
“…Many African governments also try to bridge the gap between government and civil society and strengthen the position of national government by integrating the sphere of tradition into the space of governmental power as a symbolic, legitimizing resource. Governmental leaders for instance frequently use external traditional features such as traditional regalia, titles, symbols, and myths (Lentz 1998;Van Rouveroy van Nieuwaal 1996: 43-4, 54;Von Trotha 1996: 87-88). Traditional authorities also have a role to play in the field of natural resource management.…”
Section: Negotiated or Negated?mentioning
confidence: 99%
“…Many African governments also try to bridge the gap between government and civil society and strengthen the position of national government by integrating the sphere of tradition into the space of governmental power as a symbolic, legitimizing resource. Governmental leaders for instance frequently use external traditional features such as traditional regalia, titles, symbols, and myths (Lentz 1998;Van Rouveroy van Nieuwaal 1996: 43-4, 54;Von Trotha 1996: 87-88). Traditional authorities also have a role to play in the field of natural resource management.…”
Section: Negotiated or Negated?mentioning
confidence: 99%
“…Such beliefs and moral norms are always contested in society. In her study on the legitimacy of ''big men'' in Ghana, Lentz (1998) observed a variety of differing moral values and norms based on which leaders' performance is evaluated. The existence of such different ''moral communities'' (Lentz, 1998, p. 62) emphasizes that the parameters of legitimacy are not fixed but ''debated, agreed upon or rejected within processes of social competition and/or conflict'' (Alfonso et al, 2004, p. xii).…”
Section: Legitimacy In Competitive Authoritarian Regimesmentioning
confidence: 99%
“…The existence of such different ''moral communities'' (Lentz, 1998, p. 62) emphasizes that the parameters of legitimacy are not fixed but ''debated, agreed upon or rejected within processes of social competition and/or conflict'' (Alfonso et al, 2004, p. xii). Legitimacy thus understood is not a static attribute of power but a constructed and contested notion (Alfonso et al, 2004, p. xi;Lentz, 1998).…”
Section: Legitimacy In Competitive Authoritarian Regimesmentioning
confidence: 99%
“…Rather, people are constructed in the interplay of different and often conflicting social currents, giving rise to complex and sometimes self-contradictory subjectivities, all of which make concerted action in any particular direction difficult to achieve (Kelsall, 2004). Carola Lentz, in her analysis of big men in contemporary Ghana, urges something similar when, critiquing Schatzberg, she argues that legitimacy should be thought of not as a matrix but as a plural and contested process (Lentz, 1998). See also Durham (2002) 52 See Manor (2008: 3-6).…”
Section: Caveats and Conclusionmentioning
confidence: 99%